Вдосконалення концепції відмовостійкого керування повітряним судном - Комар, М.М. (Управляющие системы и машины, 2017)
Показано результати комп'ютерного моделювання методу компенсації наслідків відмов системи автоматичного керування повітряним судном під час польоту. Розглянуто підхід, заснований на методах теорії абсолютної нелінійної інваріантності і розробку систем автоматичного керування повітряним судном з використанням теорії абсолютної інваріантності, яка дозволить реалізувати ефективний метод керування повітряним судном. Показаны результаты компьютерного моделирования метода компенсации последствий отказов системы автоматического управления воздушным судном во время полета. Рассмотрены подход, основанный на методах теории абсолютной нелинейной инвариантности, и разработка систем автоматического управления воздушным судном с использованием теории абсолютной инвариантности, что позволит реализовать эффективный метод управления судном. Purpose: The aim of this study is to demonstrate the results of computer simulation of the method for compensating the effects of the aircraft automatic control system failures during the flight. Methods: An approach is based on the methods of theory of absolute nonlinear invariance. Results: The simulation results of the horizontal stabilizer failure compensation are presented. The accident and fatality statistics from 2008 to 2016 are offered. The concept of aircraft fault tolerant control is described. Discussion: The use of the reconfiguration of the aircraft control system to guarantee its survivability during the flight is a perspective direction. However, the development of the concept of the aircraft motion control using the theory of absolute invariance allows to implement an effective developed aircraft control method that has more advantages compared with the existing methods. Conclusion: The method provides compensation for the consequences of the aerodynamic control system failures within the existing aerodynamic and functional capabilities of the aircraft, which ensures passengers comfort during the flight, reduces the load on the crew, which in its turn decreases the impact of the human factor on the flight safety in general.